SOSIALISASI PROFESI AKUNTAN DAN KELAS INTERNASIONAL AKUNTANSI PADA SEKOLAH MENENGAH ATAS DI LOMBOK TIMUR - Rizki, Novia (Jurnal Abdimas Gorontalo (JAG), 2023)
Accounting is a science that studies the preparation of financial reports and various types of financial analysis, while an accountant is a profession that carries out accounting. The accounting profession is very diverse, ranging from public accountants, corporate accountants, educator accountants, to government accountants. Each type of accounting profession has different qualifications, duties and responsibilities. For high school students, knowledge about the accounting profession is still very minimal, so socialization is needed regarding this matter. This community service activity is in the form of socialization which aims to better understand the various accounting professions so that they can strengthen them to continue studying in the accounting department.In addition to this socialization, material about international accounting classes was added, especially at the University of Mataram. The methods for implementing these service activities include preparation, preparation of materials and media, socialization, and post-socialization by evaluating activities. A positive response was given by socialization participants who were students majoring in Social Sciences who were in class XII.